2020
DOI: 10.1146/annurev-phyto-010820-012722
|View full text |Cite
|
Sign up to set email alerts
|

Gall-Inducing Parasites: Convergent and Conserved Strategies of Plant Manipulation by Insects and Nematodes

Abstract: Gall-inducing insects and nematodes engage in sophisticated interactions with their host plants. These parasites can induce major morphological and physiological changes in host roots, leaves, and other tissues. Sedentary endoparasitic nematodes, root-knot and cyst nematodes in particular, as well as gall-inducing and leaf-mining insects, manipulate plant development to form unique organs that provide them with food from feeding cells. Sometimes, infected tissues may undergo a developmental switch resulting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 147 publications
(191 reference statements)
0
42
0
Order By: Relevance
“…Similarly, Heterodera schachtii has been shown to activate the NADPH oxidases RbohD and RbohF to produce ROS, restricting infected plant cell death and promoting feeding cell formation in Arabidopsis (Siddique et al ., 2014). Ontogenesis of the RKN‐induced feeding site implies manipulation of multiple host signalling pathways to allow root to differentiate into highly metabolic, hypertrophied, and polynucleate feeding GCs, the proliferation of neighbouring cells, and de novo formation of a network of vascular tissues around the GCs (Bartlem et al ., 2014; Rodiuc et al ., 2014; Favery et al ., 2020). In addition to its function in the plant responses to biotic and abiotic stress, H 2 O 2 is indeed an important molecule transducing internal signals required for plant growth and development, in particular by interfering with hormonal signalling pathways and with the activity of target proteins such as receptor kinases and transcription factors (Černý et al ., 2018; Smirnoff & Arnaud, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Heterodera schachtii has been shown to activate the NADPH oxidases RbohD and RbohF to produce ROS, restricting infected plant cell death and promoting feeding cell formation in Arabidopsis (Siddique et al ., 2014). Ontogenesis of the RKN‐induced feeding site implies manipulation of multiple host signalling pathways to allow root to differentiate into highly metabolic, hypertrophied, and polynucleate feeding GCs, the proliferation of neighbouring cells, and de novo formation of a network of vascular tissues around the GCs (Bartlem et al ., 2014; Rodiuc et al ., 2014; Favery et al ., 2020). In addition to its function in the plant responses to biotic and abiotic stress, H 2 O 2 is indeed an important molecule transducing internal signals required for plant growth and development, in particular by interfering with hormonal signalling pathways and with the activity of target proteins such as receptor kinases and transcription factors (Černý et al ., 2018; Smirnoff & Arnaud, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…RFS caused by Ustilaginoidea virens (teleomorph: Villosiclava virens ), is a devastating grain disease in main rice planting areas worldwide, especially in China, India and Southeast Asia [ 1 , 2 ]. The occurrence of RFS can cause both serious yield loss and grain contamination by cyclopeptide mycotoxins [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effectors involved in giant cells neo-organogenesis and functioning may target different subcellular compartments and cellular host functions. Indeed, transcriptomic studies of the plant response to RKN infection have revealed that RKN can hijack several key host cellular processes, such as the cell cycle, phytohormone signaling, intercellular transport, and metabolism to favor parasitism (Caillaud et al, 2008;Gheysen and Mitchum, 2019;Favery et al, 2020).…”
Section: Introductionmentioning
confidence: 99%